Evaluasi Pelayanan Manajemen Terpadu Balita Sakit terhadap Kesembuhan Pneumonia pada Anak Balita - Nurhayati Djaswadi Dasuki, Tunjung Wibowo (Berita Kedokteran Masyarakat (BKM), 2010)
Background: Infant and under-five children mortality remains a major problem in Indonesia, especially caused by infectious diseases such as pneumonia. Based on the 2002-2003 Indonesia’s Demographic and Health Survey, infant and under-five mortality rates are 35 per 1000 live births and 46 per 1000 live births, respectively. Nationally, Health Office has implemented Integrated Management of Childhood Illness (IMCI) in primary health centers (PHCs) since 1997 to improve the coverage of pneumonia finding in under-five children. In 2005, infant mortality rate in Jambi Province was still high, that is, 41 per 1000 live births while infant mortality rate in Bungo District was 93 per 6108 live births 15,2%. Each year, there are 9 babies and 1 under five child that die and for the average there is one under five child (10%) who die because of pneumonia. In other words, there are three under five children who die every year in primary health center due to pneumonia. To avoid the death of infant and under five children, primary health center should implement standard IMCI program, yet in field it has still been facing obstacles and constraints.Objective: To investigate the results of standard IMCI service toward the recovery of under-five pneumonia in primary health centers of Bungo District in 2007.Method: This was a prospective cohort study. Sampling technique was purposive sampling. There were two groups in this study, namely case group which was exposed with the standard IMCI service and group which was exposed with non standard IMCI service. One hundred and twenty-four subjects were under-five children 2 months-5 years of age presenting pneumonia with α = 0.05 and β = 20%. Data were analyzed with univariable, bivariable, and multivariable analyses logistic regression and hypothesis test used was chi-square with p<0.05, CI 95%.Results: There was a significant relationship between the standard IMCI service, the distance to the PHC and the mothers’ education and the recovery of under-five pneumonia (OR=3.14 CI 95%=1.59-6.21 p=0.00; OR=1.68 CI 95%=1.09-2.57 p=0.00; OR=0.57 CI 95%=0.35-0.92 p=0.02, respectively). However, family income had an insignificant relationship with under-five pneumonia.Conclusion: The standard IMCI services have a greater chance toward the recovery of under-five pneumonia compared to non standard IMCI services.Keywords: services, standard, IMCI, recovery, pneumonia, under-five children